Komparasi Filsafat Pendidikan Imam Abu Bakar Arrozi Dan Imam Ibnu Bajjah - Yusuf, Mochamad; Hilman Hindami, Qoidy (AL MURABBI, 2024)
The discourse on Islamic educational philosophy has its roots in the integration of Greek reasoning with Islamic thought, giving rise to prominent Muslim philosophers. This study examines the philosophical perspectives of Imam Abu Bakar Al-Razi and Imam Ibn Bajjah on education, focusing on their contributions and relevance in modern and non-modern contexts. Both figures, known for their intellectual legacies in philosophy and science, have provided unique insights into the interplay between reason, religion, and human development. This qualitative study employs a library research approach, utilizing data from books, journals, and scholarly articles relevant to the educational philosophies of Al-Razi and Ibn Bajjah. Data were analyzed descriptively to identify their educational principles and their broader implications for contemporary educational practices. The findings reveal that Al-Razi emphasizes the role of reason and naturalism in education, advocating for a balance between intellect and spiritual growth. His "Five Eternal Principles" (al-Mabadi' al-Qadimah al-Khamsah) underline the integration of divine, material, and rational dimensions in human development. Meanwhile, Ibn Bajjah offers profound insights into individual intellectual growth through his concepts of 'uzlah (solitude) and the development of reason ('aql) as a means to achieve human perfection. His metaphysical and ethical frameworks highlight the necessity of aligning education with the innate potential of the soul, fostering intellectual independence and moral rectitude. The study concludes that the philosophies of Al-Razi and Ibn Bajjah remain pertinent in addressing contemporary educational challenges. Al-Razi’s emphasis on reason and naturalism aligns with modern scientific inquiry, while Ibn Bajjah’s advocacy for intellectual autonomy resonates with the need for critical thinking in education. The implications of their thought encourage a holistic educational approach that bridges traditional wisdom and modern methodologies